2015
DOI: 10.1039/c5pp00147a
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic inactivation of Escherichia coli with cationic ammonium Zn(ii) phthalocyanines

Abstract: The aim of this work was the development of a family of novel water soluble Zinc(II) phthalocyanines (Pc) for the photodynamic inactivation of Gram-negative bacteria. Pc derivatives 1a, 2a and 3a containing trimethylammonium groups with varied number and nature of the groups at peripheral positions were synthesized by cyclotetramerization of dimethyl amino substituted phthalonitriles in the presence of zinc powder, using 1-chloronaphthalene as a solvent, followed by cationization using dimethyl sulfate. The so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…As hypothesised, the ammonium groups of the ZnPc 1 a – 2 a improves the photoinactivation rate and may have led to an increase in the PDI efficiency due to their ability to interact electrostatically through the peripheral positive charge of the PS and the cell‐wall of Gram‐negative bacterium. Also, an increase in the number of ammonium groups, can enhance electrostatic repulsion between these molecules (avoiding aggregation behaviour) and, at the same time, it influences their cell target sites, which altogether can contribute to improve the PDI efficiency ,,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As hypothesised, the ammonium groups of the ZnPc 1 a – 2 a improves the photoinactivation rate and may have led to an increase in the PDI efficiency due to their ability to interact electrostatically through the peripheral positive charge of the PS and the cell‐wall of Gram‐negative bacterium. Also, an increase in the number of ammonium groups, can enhance electrostatic repulsion between these molecules (avoiding aggregation behaviour) and, at the same time, it influences their cell target sites, which altogether can contribute to improve the PDI efficiency ,,…”
Section: Resultsmentioning
confidence: 99%
“…The cellular localization and preferential binding sites are strongly influenced by the molecular structure as well as the nature, number and distribution of charges on the PS. A recent study of our research group revealed that an increase in the number of ammonium groups on ZnPc improves the photoinactivation rate of these derivatives towards Gram‐negative bacteria ,. Following our interest in the development of efficient PDI photosensitizers, we hypothesise that this can exhibit strong influence in the production of 1 O 2 and PDI efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…ZnPc derivatives containing trimethylammonium groups with a varied number and nature of the groups at peripheral positions were described by the Tomé group [43] . The photosensitizing potential of these compounds against a recombinant bioluminescent E. coli strain was shown to be dependent on the nature of the neighbouring group.…”
Section: Molecular Photosensitizersmentioning
confidence: 99%
“…Also, antimicrobial efficiency of ZnPcs has been tested as in vivo animal models for clinical trials [35,36]. In our previous studies it is observed that synthesized ZnPc has highly promising PDT agent for cancer treatment [23,35,[37][38][39]. For this reason, we have examined APDT efficiency of synthesized ZnPc and ZnPc-TiO 2 in this article.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the literature have shown that cationic charges of PSs are more effective [21][22][23]. In addition, this accumulation occurs faster in microbial cells and could selectively bind to these microorganisms while PS accumulation is slow in normal mammalian cells [24].…”
Section: Introductionmentioning
confidence: 99%